Effect and mechanism of resveratrol against polycystic ovary syndrome: a review - Chang, Hui; Shi, Baichao; Wang, Yu; Lu, Fengjuan; Guan, Muxin; Wu, Xiaoke (Frontiers in Endocrinology, 2025)
Polycystic ovary syndrome (PCOS) is a prevalent reproductive endocrine disorder characterized by significant clinical heterogeneity. The etiology of PCOS remains elusive, though it is closely linked to genetic, metabolic, endocrine, and environmental determinants. Resveratrol, a natural polyphenol, has garnered considerable interest due to its diverse biological activities. While resveratrol has been shown to ameliorate disorders in glucose, lipid, and endocrine metabolism associated with PCOS, the precise underlying mechanisms remain unclear. This narrative review aims to explore the potential mechanisms through which resveratrol operates, considering the multifaceted pathological pathways of PCOS, thereby offering insights for clinical applications and drug development.